Retrotracheal Extraskeletal Ewing’s Sarcoma: Case Report and Discussion on Airway Management - Graeme Van Der Meer; Hannah Linkhorn; Maayan Gruber; Murali Mahadevan; Colin Barber (Turkish Archives of Otorhinolaryngology, 2017)

(untitled)
Extraskeletal Ewing’s sarcoma is a rare tumor, and the management of airway compromise in case of cervical Ewing’s sarcoma has not been established. This report describes the case of a patient with retrotracheal Ewing’s sarcoma and discusses a successful approach to airway management. A 12-year-old male presented with a 2-week history of sore throat and sleep-disordered breathing and 48 hours of stridor. Imaging confirmed a retrotracheal soft tissue mass with airway compromise. A planned and controlled approach to his airway management resulted in a secure airway prior to definitive treatment.